Association of Acute Alteration of Consciousness in Patients With Acute Ischemic Stroke With Outcomes and Early Withdrawal of Care. (5th April 2022) - Alkhachroum, Ayham; Bustillo, Antonio J.; Asdaghi, Negar; Ying, Hao; Marulanda-Londono, Erika; Gutierrez, Carolina M.; Samano, Daniel; Sobczak, Evie; Foster, Dianne; Kottapally, Mohan; Merenda, Amedeo; Koch, Sebastian; et al.
Abstract : Background and Objectives: Early consciousness disorder (ECD) after acute ischemic stroke (AIS) is understudied. ECD may influence outcomes and the decision to withhold or withdraw life-sustaining treatment. Methods: We studied patients with AIS from 2010 to 2019 across 122 hospitals participating in the Florida Stroke Registry. We studied the effect of ECD on in-hospital mortality, withholding or withdrawal of life-sustaining treatment (WLST), ambulation status on discharge, hospital length of stay, and discharge disposition. Results: Of 238, 989 patients with AIS, 32, 861 (14%) had ECD at stroke presentation. Overall, average age was 72 years (Q1 61, Q3 82), 49% were women, 63% were White, 18% were Black, and 14% were Hispanic. Compared to patients without ECD, patients with ECD were older (77 vs 72 years), were more often female (54% vs 48%), had more comorbidities, had greater stroke severity as assessed by the National Institutes of Health Stroke Scale (score ≥5 49% vs 27%), had higher WLST rates (21% vs 6%), and had greater in-hospital mortality (9% vs 3%). Using adjusted models accounting for basic characteristics, patients with ECD had greater in-hospital mortality (odds ratio [OR] 2.23, 95% CI 1.98–2.51), had longer hospitalization (OR 1.37, 95% CI 1.33–1.44), were less likely to be discharged home or to rehabilitation (OR 0.54, 95% CI 0.52–0.57), and were less likely to ambulate independently (OR 0.61, 95% CI 0.57–0.64). WLST significantly mediated the effect of ECD on mortality (mediation effect 265; 95% CI 217–314). In temporal trend analysis, we found a significant decrease in early WLST (<2 days) (R 2 0.7, p = 0.002) and an increase in late WLST (≥2 days) (R 2 0.7, p = 0.004). Discussion: In this large prospective multicenter stroke registry, patients with AIS presenting with ECD had greater mortality and worse discharge outcomes. Mortality was largely influenced by the WLST decision.